Temperature-dependent effects of hip bath on primary dysmenorrhea individuals: A randomized controlled trial - JS, Ajmi; Shetty, Geetha B; KJ, Sujatha; Shetty, Prashant (Indian Journal of Integrative Medicine, 2024)
Background & Aim: To evaluate the specific Temperature Effect of the hip bath on primary dysmenorrhea. The current study aimed to determine whether a specific temperature hip bath can ease the discomfort associated with primary dysmenorrhea. Experimental Procedure: A cohort of 160 young women, aged between 16 to 25, who had been diagnosed with primary dysmenorrhea, were selected and randomly divided into three groups Cold hip bath (CHB), Hot hip bath (HHB), Neutral hip bath (NHB). The participants were evaluated using a menstrual symptom questionnaire (MSQ), a visual analog scale (VAS), and a hemogram at baseline and after the three-month intervention. It was registered under the clinical trial registry of India (CTRI/2021/12/038381). Results: After the intervention, CHB demonstrated a highly significant reduction in VAS score (P < 0.01) and MSQ (P < 0.01) when compared to the other two groups after the 3 months of intervention. The complete blood count showed a significant increase in hemoglobin and red blood cells and a reduction in eosinophils and lymphocytes. Conclusion: According to the study, a Cold Hip bath is a safe and effective way to relieve primary dysmenorrhea pain compared to neutral or hot-temperature hip baths. Participants experienced reduced menstrual pain intensity and improved symptoms after a three-month intervention.